Effectiveness of Different Preventive Programs in Cariogram Parameters of Young Adults at High Caries Risk - Said Karabekiroğlu; Nimet Ünlü (Hindawi Limited, 2017)
Objective. To evaluate the effectiveness of different preventive programs in young adults at high caries risk using Cariogram software. Methods. Sixty-six young adults with high caries risk were evaluated. Dental caries risk for all subjects was determined according to WHO criteria. Subjects were divided into three different preventive groups (control: OH, fluoride varnish: FV, and chlorhexidine varnish: CV). They were followed for 12 weeks (baseline: T0, 1 week: T1, 4 weeks: T2, and 12 weeks: T3). Plaque index, diet frequency, and salivary chairside tests (to record the flow rate, buffer capacity, and mutans streptococci and lactobacillus counts) were performed at each visit. Based on these data, ten caries-related variables were collected and inserted into the Cariogram software to calculate the predicted chance of avoiding caries for each subject. Results. Significant changes were obtained about the Cariogram parameters (diet, bacteria, susceptibility, circumstances, and Cariogram risk group). No significant differences were found between the three methods regarding mean Cariogram scores after 3 months (p>0.05). Conclusions. The regular and effective short-term (three months) use of 1450 ppm fluoridated toothpaste, one visit application of fluoride, and chlorhexidine varnishes were effective for reducing caries risk in young adults, which can be clearly demonstrated using Cariogram software.